Axial chirality in biaryl N, N‐dialkylaminopyridine derivatives bearing an internal carboxy group. Issue 5 (5th March 2020) - Nishino, Reiko; Hamada, Shohei; Elboray, Elghareeb E.; Ueda, Yoshihiro; Kawabata, Takeo; Furuta, Takumi
Abstract: Axial chirality in N, N ‐dimethylaminopyridines as well as N, N ‐dipropylaminopyridines bearing an internal carboxy group were evaluated based on their racemization barriers and circular dichroism spectra. The half‐life of racemization of N, N ‐dipropylaminopyridine derivative 2 was estimated to be 19.7 days at 20°C. Its enantiomers isolated as optically active forms showed positive‐negative and negative‐positive Cotton effects for (+)‐2 and (−)‐2, respectively, from 310 to 210 nm. Furthermore, (−)‐2 was applied as a chiral nucleophilic catalyst and exhibited asymmetric induction in acylative kinetic resolution of 1‐(1‐naphthyl)ethane‐1‐ol. Abstract :